ANALISIS FAKTOR-FAKTOR FUNDAMENTAL KEUANGAN TERHADAP RISIKO DAN RETURN PERUSAHAAN INDUSTRI TEKSTIL DAN PRODUK TEKSTIL DI INDONESIA - noerchoidah, noerchoidah; harryono, sumadji (Fakultas Ekonomi Universitas PGRI Adi Buana, 2018)
This study aims to obtain empirical evidence that the company's financial fundamentals have a significant influence both together and partial toward return and beta share on Textile and Product Textile Industry that listing on the Indonesian Stock Exchange. As an independent variable used is the Earning Per Share (EPS), Dividend Payout Ratio (DPR), Current Ratio (CR), Return on Investment (ROI) and Price Earning Ratio (PER). While the dependent variable is the stock return and beta. Testing linear regression of stock return produce the F-count of 0213 with a significance level of 0,951 and against beta stocks produce F-count is 4.748 with a significance level of 0.010. This means that simultaneously the company's financial fundamentals have no significant effect on stock returns at a significance level of 5%, while against beta stocks have a significant influence on the level of significance of 5%. Tests partially with t-test showed that none of the company's financial fundamentals variables significantly influence the stock return at 5% significance level. While in beta testing on the stock, shares that have a significant effect on ROI level 5% only, whereas other variables did not influence significantly